Bioequivalence of Two Lansoprazole Delayed Release Capsules 30 mg in Healthy Male Volunteers under Fasting, Fed and Fasting-applesauce conditions: A Partial Replicate Crossover Study Design to Estimate the Pharmacokinetics of Highly Variable Drugs - Thota, S.; Khan, S. M.; Tippabhotla, S. K.; Battula, R.; Gadiko, C.; Vobalaboina, V. (Drug Research, 2013)
An open-label, 2-treatment, 3-sequence, 3-period, single-dose, partial replicate crossover studies under fasting (n=48), fed (n=60) and fasting-applesauce (n=48) (sprinkled on one table spoonful of applesauce) modalities were conducted in healthy adult male volunteers to evaluate bioequivalence between 2 formulations of lansoprazole delayed release capsules 30 mg. In all the 3 studies, as per randomization, either test or reference formulations were administered in a crossover manner with a required washout period of at least 7 days. Blood samples were collected adequately (0–24 h) to determine lansoprazole plasma concentrations using a validated LC-MS/MS analytical method. To characterize the pharmacokinetic parameters (Cmax, AUC0–t, AUC0–∞, Tmax, Kel and T1/2) of lansoprazole, non-compartmental analysis and ANOVA was applied on ln-transformed values. The bioequivalence was tested based on within-subject variability of the reference formulation. In fasting and fed studies (within-subject variability>30%) bioequivalence was evaluated with scaled average bioequivalence, hence for the pharmacokinetic parameters Cmax, AUC0–t and AUC0–∞, the 95% upper confidence bound for (μT−μR)2−θσ2WR was ≤0, and the point estimates (test-to-reference ratio) were within the regulatory acceptance limit 80.00–125.00%. In fasting-applesauce study (within-subject variability<30%) bioequivalence was evaluated with average bioequivalence, the 90% CI of ln-transformed data of Cmax, AUC0–t and AUC0–∞ were within the regulatory acceptance limit 80.00–125.00%. Based on these aforesaid statistical inferences, it was concluded that the test formulation is bioequivalent to reference formulation.
Keywords: lansoprazole; partial replicate study; scaled average bioequivalence; within-subject variability